2022
DOI: 10.3389/fnut.2022.906227
|View full text |Cite
|
Sign up to set email alerts
|

Chilling injury of tomato fruit was alleviated under low-temperature storage by silencing Sly-miR171e with short tandem target mimic technology

Abstract: In this study, the role of Sly-miR171e on post-harvest cold tolerance of tomato fruit was researched. The results showed that overexpression of Sly-miR171e (miR171e-OE) promoted postharvest chilling injury (CI) of tomato fruit at the mature red (MR) and mature green (MG) stage. Contrasted with the wild type (WT) and miR171e-OE fruit, the knockdown of Sly-miR171e (miR171e-STTM) showed a lower CI index, lower hydrogen peroxide (H2O2) content, and higher fruit firmness after harvest. In the fruit of miR171e-STTM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Totally, we identified 122 miRNA‐cleaved targets, including DCL1 , REV , ARF10, GRF4 , and GRAS24 , which were cleaved by miR162, miR165/miR166, miR160, miR396, and miR171, respectively (Figure 6b, Table S6). Among these targets, GRAS24 was previously shown to increase in expression in tomato when its endogenous Sly‐miR171d or Sly‐miR171e was silenced, resulting in improved chilling resistance (Xing et al., 2022; Zhao et al., 2022). Our GMUCT profiling validated the miR171 cleavage at GRAS24 in tomato.…”
Section: Resultsmentioning
confidence: 99%
“…Totally, we identified 122 miRNA‐cleaved targets, including DCL1 , REV , ARF10, GRF4 , and GRAS24 , which were cleaved by miR162, miR165/miR166, miR160, miR396, and miR171, respectively (Figure 6b, Table S6). Among these targets, GRAS24 was previously shown to increase in expression in tomato when its endogenous Sly‐miR171d or Sly‐miR171e was silenced, resulting in improved chilling resistance (Xing et al., 2022; Zhao et al., 2022). Our GMUCT profiling validated the miR171 cleavage at GRAS24 in tomato.…”
Section: Resultsmentioning
confidence: 99%
“…In general, microRNAs (miRNAs) are a class of small, nonprotein coding RNA molecules that function as negative regulators of target gene messages (Hinske et al, 2010), and their negative modulations on target genes are essential for enhancing cold tolerance (Zhao et al, 2022). Xing et al investigated the mechanism of action of Sly-miR171d on chilling injury in tomato fruit.…”
Section: Genetic Improvement Of Cold Tolerance In Horticultural Cropsmentioning
confidence: 99%
“…Silencing of Sly-miR171d or Sly-miR171e with STTM was performed according to Yan et al [63]. Primary transgenic plant (T0) was generated by Agrobacterium tumefaciens-mediated transformation according to Zhao et al [22]. Three STTM-miR171d and STTM-miR171e lines were selected from the T1 and T2.…”
Section: Transformation Of Tomato Plantmentioning
confidence: 99%
“…It has been documented that SlGRAS24 is a key transcription factor coordinating the regulation of GA signaling pathways in tomato, and the HAM genes may be regulators of endogenous GA balance in SAM, RAM, and axillary meristem to control the maintenance of meristem and generation of organs [20]. In previous studies, it was found that silencing of miR171d and miR171e enhanced the cold tolerance of tomato fruit by targeting SlGRAS24 to regulate GA signaling [21,22].…”
Section: Introductionmentioning
confidence: 99%